Outcomes of Spontaneous Labor in Women Undergoing Trial of Labor after Cesarean as Compared with Nulliparous Women: A Retrospective Cohort Study - Lassey, Sarah C.; Robinson, Julian N.; Kaimal, Anjali J.; Little, Sarah E. (American Journal of Perinatology, 2018)
Objective The objective of this study was to compare spontaneous labor outcomes in women undergoing trial of labor after cesarean (TOLAC) and nulliparas to better counsel women.Study Design A 4-year retrospective cohort. We included women at term in spontaneous labor with vertex singletons and no more than one prior cesarean delivery. In planned secondary analysis, we focused on a subset of women with a prior cesarean and a predicted likelihood of a successful vaginal delivery of 70% or more based on the Maternal-Fetal Medicine Units-vaginal birth after cesarean (VBAC) calculator.Results Our cohort included 606 TOLACS and 606 nulliparas. Women undergoing TOLAC were more likely to undergo cesarean delivery (25.7 vs. 14.7%; p < 0.001). Severe maternal hemorrhage (1.5 vs. 0.2%; p = 0.02) and uterine rupture (1.9 vs. 0.0%; p < 0.01) were more likely in the TOLAC group. For the subset of women with a predicted likelihood of VBAC of 70% or more, there were no differences in cesarean delivery (16.7 vs. 14.7%; p = 0.51), maternal, or immediate neonatal complications.Conclusion Women undergoing TOLAC were more likely to have a cesarean delivery, hemorrhage, or uterine rupture. Those with more than 70% predicted likelihood of VBAC were no more likely to experience these outcomes. These findings help contextualize the risks of TOLAC for women considering this option.
Keywords: TOLAC; VBAC; maternal; neonatal; outcomes